Strategic Perspective Needed in T&D Asset Management. Issue 10 (May 2016) - Rich, Jonathan; Sudarshan, Pallav; Bertrand, Leonard
Abstract : At an increasing pace, power system outages are destroying billions of dollars in value every year. The United States endures more blackouts than any other developed nation, with the number of incidents and hours of outage increasing steadily for the past few decades.